Rural-urban migration, structural transformation, and housing markets in China - Garriga, Carlos (2023)
This paper investigates the interrelationship between urbanization, structural transformation, and the post-2000 Chinese housing boom through the lens of a dynamic spatial equilibrium model that features migration and a rich housing market structure with mortgages. Urbanization and structural transformation emerge as key drivers of China’s house price boom, while at the same time rising house prices impede these forces of economic transition. Policies to boost urbanization can be undone by the endogenous price response. Land supply expansion ameliorates this negative feedback. Overall, housing markets powerfully shape the path of economic development.